miR-125b affects mitochondrial biogenesis and impairs brite adipocyte formation and function - Giroud, Maude; Herzig, Stephan; Scheideler, Marcel (Molecular metabolism, 2016)
miR-125b-5p levels negatively correlate with UCP1 expression in rodent and human. miR125b levels in white adipose tissue are positively correlated with BMI. miR-125b-5p modulates oxygen consumption. Mitochondriogenesis is controlled by miR-125b-5p. In vivo modulation of miR-125b-5p controls brown and brite adipocyte formation.
Gesehen am 26.03.2018